Accumulation conditions and rolling exploration results in the periphery of "Deep Sea No. 1" giant gas field in central canyon of Qiongdongnan Basin - Kui CHEN; Wenjuan WANG; Wanxing XU; Zhandong JIANG; Kedong SHU; Anmin HUANG (Shiyou shiyan dizhi, 2023)
In order to explore high-quality proven geological reserves for the "Deep Sea No.1" giant gas field in the central canyon of the Qiongdongnan Basin and promote the sustainable development of the giant gas field, the rolling exploration technology is innovatively introduced into the deep-water natural gas exploration in the central canyon. The main gas-bearing strata such as the Upper Miocene Huangliu Formation and the Pliocene Yinggehai Formation on the periphery of mature exploration area of the gas field are studied. Five potential blocks are searched for rolling exploration, and Block 4 with superior reservoir forming conditions and the ability to control geological reserves is selected. The reservoir forming conditions of T29B and T29E sand bodies in the Yinggehai Formation, upper HL-Ⅰ, HL-Ⅲ and HL-Ⅳ gas groups in the Huangliu Formation are studied. By analogy with drilling data and accumulation rules of the surrounding wells, the accumulation conditions such as trap, reservoir deposition and oil and gas migration and accumulation of Block 4 are studied. The T29E sand bodies of the Huangliu Formation and the Yinggehai Formation in Block 4 are all lithologic traps formed by the joint closure of the central canyon channel bank and the weak-amplitude muddy channel in the later stage of the canyon. The T29B sand body is an anticline trap formed by the local high point of the submarine fan under the canyon background. Through the amplitude attribute sand body characterization and forward modeling, the reservoir-seal combination of the target layer of the Huangliu and Yinggehai formations in Block 4 is well implemented. The vertical migration modes such as diapirs, high-angle fractures and micro-fractures are migrated to the target layer traps, and the effectiveness of the top and bottom plates of the traps is good, thus playing a good role in preserving oil and gas. According to the accumulation factors, the resource parameters and potential resources are implemented, and the deployment of deep-water rolling exploration wells is carried out. The deep-water directional drilling technology is innovatively introduced, and the well L17-10d is deployed to implement the gas-bearing strata and reserve scale as much as possible, and good drilling results are achieved. The well L17-10d encountered a pure gas layer in the T29B, T29E sand bodies and the HL-Ⅲ gas group. The vertical thickness of the gas layer was nearly 45 m, and the proven geological reserves were nearly 7 billion cubic meters. It further confirmed the accumulation law of the deep water area of the central canyon, pointed out the direction for the rolling exploration of the surrounding area, promoted the production of proven geological reserves and controlled geological reserves of some difficult-to-produce natural gas, and provided a strong guarantee for the subsequent sustainable development of the "Deep Sea No.1" giant gas field.